Metal Emissions and Urban Incident Parkinson Disease: A Community Health Study of Medicare Beneficiaries by Using Geographic Information Systems - Willis, Allison W. (Oxford University Press, 2010)
Parkinson disease associated with farming and exposure to agricultural chemicals has been reported in numerous studies; little is known about Parkinson disease risk factors for those living in urban areas. The authors investigated the relation between copper, lead, or manganese emissions and Parkinson disease incidence in the urban United States, studying 29 million Medicare beneficiaries in the year 2003. Parkinson disease incidence was determined by using beneficiaries who had not changed residence since 1995. Over 35,000 nonmobile incident Parkinson disease cases, diagnosed by a neurologist, were identified for analysis. Age-, race-, and sex-standardized Parkinson disease incidence was compared between counties with high cumulative industrial release of copper, manganese, or lead (as reported to the Environmental Protection Agency) and counties with no/low reported release of all 3 metals. Parkinson disease incidence (per 100,000) in counties with no/low copper/lead/manganese release was 274.0 (95% confidence interval (CI): 226.8, 353.5). Incidence was greater in counties with high manganese release: 489.4 (95% CI: 368.3, 689.5) (relative risk = 1.78, 95% CI: 1.54, 2.07) and counties with high copper release: 304.2 (95% CI: 276.0, 336.8) (relative risk = 1.1, 95% CI: 0.94, 1.31). Urban Parkinson disease incidence is greater in counties with high reported industrial release of copper or manganese. Environmental exposure to metals may be a risk factor for Parkinson disease in urban areas.